Actinobacteria Diversity, Applications and Medical Aspects - Hozzein, Wael N. (IntechOpen, 2022)
This book provides in-depth insights into the diversity of actinobacteria, their various medical aspects, and their biotechnological applications. It is aimed at graduate students and researchers working with actinobacteria who need to know about recent advances in their research fields. The book, which is divided into four sections, contains 13 chapters that review the most recent methods, discuss various applications of actinobacteria, introduce some interesting results, and explore future prospects for the topics covered.